Application Of Problem Based Learning Model In Civics Learning On Central Government Structure Material In Grade IV Of Pabelan Kartasura State Elementary School - Afifah Setyawati; Ajeng Nurhidayah; Asyifaa Jasmine Priyani P; Rawanoko, Endrise Septina (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
This research is entitled "Application of the Problem Based Learning Model in Civics Learning on Central Government Structure Material Class IV Sdn Pabelan Kartasura" This research aims to analyze the application of the Problem Based Learning (PBL) learning model in Civics Education (PKn) learning on Central Government Structure material in class IV SDN Pabelan, Kartasura. This research is motivated by the need to increase students' active participation and in-depth understanding of abstract material. The PBL model also encourages students to be more active in discussing, working together, and solving problems independently or in groups. The research results show that the application of the PBL model can increase student involvement in the learning process, critical thinking skills, and student learning outcomes. The research methods used are direct observation in class, interviews with teachers, and documentation. The observation results show that Civics learning in class IV at SDN Pabelan 03 has been implemented in accordance with the learning plan prepared. Teachers use lecture, question and answer and group discussion methods to improve students' understanding of the material. Learning evaluation is carried out through written tests and student attitude assessments. Obstacles found included limited time and lack of student involvement in several discussion activities. The conclusion from this observation is that Civics learning at SDN Pabelan 03 has gone well, but innovation is needed in learning methods and media to improve the quality of learning.